Measurements of Implant Stability Following Sinus Lift: A Pilot Clinical Study - Muhamed Ajanović; Alma Kamber-Ćesir; Adis Hamzić; Selma Tosum (Acta Stomatologica Croatica, 2015)
Aim: The aim of this study was to evaluate the implant stability of Bredent Sky Blue implants of different diameters following one stage sinus lift procedure. Material and methods: This study included 9 male patients with an existing indication for unilateral or bilateral sinus lift procedure. As grafting materials, combination of allograft material MinerOss® cortical & cancellous and Ossceram nano were used. Results: All implants were considered successful and ISQ levels were measured by Osstell ISQ device. The ISQ values were from 68 to 84. The mean values of stability of Bredent Sky Blue implants of different diameters following one stage sinus lift procedure were 77.73 ± 2.93 (MD) and 77.98 ± 2.72 (VO).